Health-related quality of life and fatigue in adult rare bone disease patients: A cross-sectional study from Austria - Behanova, Martina; Medibach, Amadea; Haschka, Judith; Kraus, Daniel; Raimann, Adalbert; Mindler, Gabriel T.; Zwerina, Jochen; Kocijan, Roland (Bone (New York, N.Y.), 2024)
To assess physical and mental health domains of health related quality of life (HRQoL) as well as fatigue in rare bone disease (RBD) patients and to compare to patients with osteoporosis (OPO) and healthy controls (CTRL) without known bone diseases and to study associations of Fatique Severity Scale (FSS) with eight domains of HRQoL. Monocentric, cross-sectional study carried out between 2020 and 2022 in a hospital affiliated with the Vienna Bone and Growth Center (European Reference Network Center for Rare Bone Disease) in Vienna, Austria. The study comprised three types of RBD: Osteogenesis imperfecta, Hypophosphatasia and X-linked Hypophosphatemia. Fatigue was assessed by FSS. The higher score indicates more fatigue severity. HRQoL was assessed by Short-Form Health Survey (SF-36 v2). Physical component (PCS) and mental component summary scores (MCS) were calculated and normalised to a general population. A higher score indicates better HRQoL. Age-adjusted ANCOVA was used to assess differences in PCS and MCS between groups. Spearman correlation was used for associations of FSS with eight domains of HRQoL. Study comprised 50 RBD patients [Mean age (SD) 48.8 (±15.9), 26 % male], 51 OPO patients [66.6 (±10.0), 9.8 % male] and 52 controls [50.8 (±16.3), 26.9 % male]. RBD patients had significantly higher mean age-adjusted FSS (3.5, 95 % CI 3.1–4.0) than controls (2.6, 95 % CI 2.2–3.0, p = 0.008), but not in comparison to osteoporotic patients 2.6 (95 % CI 2.2–3.0, p = 0.69). Diminished age-adjusted PCS of HRQoL was observed in RBD patients with a mean score of 37.1 (95 % CI 33.4–40.8), whereas their MCS of 50.1 (95 % CI 46.6–53.7) was comparable to controls (52.9, 95 % CI 49.8–56.0) and osteoporotic patients (50.2, 95 % CI 45.4–54.9). FSS score was negatively correlated with physical and mental component in RBD (ρ = −0.37, p < 0.05 and ρ = −0.54, p < 0.01, respectively) and OPO patients (ρ = −0.37, p < 0.05 and ρ = −0.35, p < 0.01, respectively). The HRQoL in adult patients with rare bone diseases is lower than compared to osteoporotic and control group in this Austrian population. Fatigue has significant negative impact on HRQoL and it is important to address it when meeting with RBD patients in clinical practice. •Rare bone disease patients exhibit higher fatigue levels than controls.•Physical health domains of health-related quality of life are notably diminished in rare bone disease patients.•Mental health domains are similar in rare bone disease patients, osteoporotic patients and controls.•Fatigue was negatively correlated with physical and mental component.•Managing fatigue is crucial for improving health-related quality of life in patients with rare bone diseases.